Muscle Energy Technique, Stretching and Strengthening on Hip Rotation Range and Kick Distance in Football Players with Adductor Related Groin Pain (International Journal of Physiotherapy, 2021)
Background: Football is a commonly played team sport, and kicking is the primary skill needed. The incidence of adductor strain is high in football players, and thus their kick distance is affected due to groin pain. This indicates the importance of stretching and strengthening exercises as a necessary therapeutic technique to treat these sportspeople.Objective: To compare the effectiveness of muscle energy techniques (MET), stretching and strengthening exercises on hip rotation, and kick distance.Design: Randomized Control Trial.Methods: Forty football players suffering from groin pain due to adductor strain were selected from five professional soccer clubs in Jazan, Saudi Arabia, and randomized into two equal groups. Affected hip joint rotation [Internal + External Rotation] range, instep kick, and sidekick distances were measured and documented as baseline values. In addition, group A received MET, stretching, and strengthening exercises, whereas group B received only stretching and strengthening exercises for six weeks. Post-test values of the outcome measures were recorded at the end of the intervention.Results: Statistical comparison of the results between the groups showed that the MET group had significant improvement than the strengthening and stretching group in the hip rotation range (p